Gambaran Tentang Pemujaan Dalam Prasasti Batur Masa Majapahit - Hardianti Hardianti (JURNAL PANALUNGTIK, 2021)
In general, the Batur inscription tells of the tradition of worshiping ancestors accompanied by the division of worship times among the descendants of their ancestors. Worship is carried out by the inhabitants of Kabuyutan Kalyasĕm and the mandalas around the Hyang Mountains. This study aims to determine the continuity of worship in the Hyang Mountains region along with the lives of its worshipers. The problem that will be discussed is how is the description of worship in the Batur inscription including chronology and who is the main character being worshiped? The conclusion of this research is that there is a continuity of worship as told in the Batur inscription that has been going on since the reign of Ratu Tribhuwana Tunggadewi, continuing during the reign of King Hayam Wuruk until the end of the Majapahit reign. Revered figures are the founders of Kabuyutan and the mandalas around the Hyang mountains with the main character who is worshiped is someone called Sang Hyang Kabuyutan i Kalyasĕm. The religions practiced by residents in religious places around the Hyang Mountains vary, namely: Hindu Saiwa, Indigenous Religions and Tantra. Other evidence to support the existence of worship as told in the Batur Inscription can be found in the Nagarakrtagama and Tantu Panggelaran Books. The method used is a qualitative method with a historical archaeological study consisting of several stages: data collection, source criticism, interpretation and historiography.